2009
DOI: 10.1111/j.1538-7836.2009.03300.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic agents doxorubicin and epirubicin induce a procoagulant phenotype on endothelial cells and blood monocytes

Abstract: Summary.  Background: Although chemotherapy is associated with an increased risk of thrombosis, the pathogenic mechanisms by which chemotherapeutic agents exert prothrombotic effects are unclear. Objectives: In this study we explored the possibility that chemotherapeutic agents doxorubicin, epirubicin, 5‐fluorouracil and methotrexate induce a procoagulant phenotype on vascular endothelial cells and/or on blood monocytes. Methods: Thrombin generation was measured in defibrinated plasma exposed to chemotherapy‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 31 publications
3
52
0
1
Order By: Relevance
“…What is more, our results provide coherent evidence that elevated PLR was of a strong predictor of thrombosis in patients with cancers [12]. In previous studies, the platelet counts alone have been reported as an independent risk factor for cancer related VTE [24,25]. Compared to the platelet alone, our study indicated that baseline evaluation of PLR might provide important information to predict higher risk of cancer related VET.…”
Section: Discussionsupporting
confidence: 69%
“…What is more, our results provide coherent evidence that elevated PLR was of a strong predictor of thrombosis in patients with cancers [12]. In previous studies, the platelet counts alone have been reported as an independent risk factor for cancer related VTE [24,25]. Compared to the platelet alone, our study indicated that baseline evaluation of PLR might provide important information to predict higher risk of cancer related VET.…”
Section: Discussionsupporting
confidence: 69%
“…[7][8][9][10][11][12][13][14][15] In vitro, Swystun et al demonstrated that exposure of plasma to either doxorubicin-or epirubicin-treated endothelial cells resulted in an increase in plasma thrombin generation. 48 However, for the first time, in this study we have demonstrated that there is no increased endothelial response in VTEþ compared to VTEÀ patients.…”
Section: Discussionmentioning
confidence: 86%
“…We previously demonstrated in vitro that anthracyclines (doxorubicin and epirubicin) have a greater 'prothrombotic potential' than antimetabolites do (methotrexate and 5-fluorouracil) [27] . Treatment of vascular endothelial cells with either doxorubicin or epirubicin increased thrombin generation in plasma exposed to these cells.…”
Section: Discussionmentioning
confidence: 99%